Factors That Affect Career Interest as A Public Accountant - Ni Nyoman Sri Rahayu Damayanti; A.A. Pt. Agung Mirah Purnama Sari (International Journal of Education, Information Technology, and Others, 2021)
A persons’ career selection is based on the perception, personality, interests, abilities, and background of knowledge possessed by the individual. For accounting students, there are several areas of work that can be used as an alternative to career interests. In general, the desire of accounting students is to become a professional in the field of accounting. There are several factors that affect the career interest of an accounting student. Financial and non-financial aspect are two main reasons for people to choose their career. Financial award, professional recognition, behavior of the student, and the understanding of public accountant law are believed to be able to influence a persons’ career interests. The type A behavior is one type of people behavior that used as a behavior variable in this study. The respondents in this study are accounting students that already pass the 7th semester or still in 7th semester that study in the private universities in Denpasar. Data collection techniques are carried out by questionnaire method. The instruments are valid and reliable. The data already free from classical assumption problem. The data was analyzed by multiple linear regression analysis. The result showed that financial award, professional recognition, type A behavior, and the understanding of public accountant law have a positive and significant impact on career interest of accounting students as public accountant.